TAXATION APPROACHES REGARDING PRIVATE PENSION SYSTEMS (Third Sector Social Economic Review, 2019)
Understanding the taxation process of the private pension requires the evaluation of all stages of pension system. Saving, return and pension payments as stages of private pension system can also be taxed. But the taxation of these three phases without exception leads to double taxation problem. Double taxation problem will not be a subject if one or two stages are excepted from taxation. When the second phase are not subjected to taxation, taxation of either pension savings (Tax-Exempt-Exempt) or pension payments (Exempt-Exempt-Tax) will result similar effect on saving and tax revenue. These approaches mainly leave savings out of taxation, thus, we can identify these approaches as expenditure tax. In this context, we can classify taxation of pension payment as pure expenditure tax, and classify taxation of savings as prepaid expenditure tax. On the other hand, taxation of pension savings (Tax-Tax-Exempt) or taxation of pension payment (Exempt-Tax-Tax), together with the return phase taxation, also have similar effect on savings and tax revenues. Last two approaches are considered as comprehensive income tax. If we chose the first two approaches, pension funds will be higher than the funds where choosing last two approaches, because of the equality of pre-tax and post-tax returns. Organisation for Economic Co-operation and Development or European Union member states widely apply taxation of pension payments (Exempt-Exempt-Tax) approach, but significant portion of these countries tax their pension payments at a low level.
Keywords: Private pension; taxation; 3rd pillar pension.